How Images and Words Tell Stories Together: A Functional Multimodal Analysis of Let’s Read Digital Picturebooks - Alan Jaelani; Zuriyati; Miftahulkhairah Anwar (Universitas Hamzanwadi, 2026)
Although digital picturebooks have attracted increasing scholarly attention, relatively few studies have systematically applied functional image–text relation models to examine how meaning is multimodally organized, particularly in Southeast Asian open-access digital publishing contexts. This study investigates how visual and verbal modes are structurally coordinated in digital children’s literature by analyzing image–text relations and logico-semantic patterns in three adventure-themed storybooks published on the Let’s Read platform: A Cry by the Lake, Run Away to the Stars, and Which Route is Faster? Drawing on Martinec and Salway’s (2005) framework, which extends Halliday's logico-semantic principles to visual–verbal interaction, the study employs a qualitative multimodal discourse analysis. Each page containing a co-present illustration and written text was treated as a multimodal unit of analysis, resulting in a corpus of 50 pages. The findings indicate a recurrent preference for equal–complementary image–text relations, in which visual and verbal modes work interdependently to construct narrative meaning without clear modal dominance. Across the corpus, expansion relations, particularly elaboration and causal enhancement, emerge as prominent strategies for organizing narrative development, while projection–idea relations are concentrated in scenes involving imagination, reflection, and emotional realization. These patterns suggest that the selected digital picturebooks are semiotically designed to support narrative coherence and to represent experiential and interpersonal meanings through patterned visual–verbal coordination. The study highlights the analytical value of functional multimodal frameworks for examining children’s digital literature and offers theoretically grounded insights into image–text design practices in Southeast Asian open-access publishing.